Model Pembelajaran Bimbingan Belajar Saddhāphala Jaya Krecek Temanggung - Astuti, Puji; Sukodoyo, Sukodoyo; Kustiani, Kustiani (Jurnal Pencerahan, 2018)
Abstract Researchers examined more about the learning guidance learning model to find out the learning model used by the teacher in the learning process at Saddhphala Jaya Krecek. This research uses descriptive qualitative method. Data collection techniques and instruments used are using interview, observation and documentation techniques. Technique of validating data through continuous observation, postulation, and member check. Data were analyzed using the Miles and Huberman method, namely collection, data reduction, data presentation, and conclusion drawing or data verification. The results of this study that learning conducted in the Saddhāphala Jaya Krecek includes the opening stage (Namakārapāṭha), presentation of material, and closing or evaluation; (2) the model used by the teacher depends on the activities carried out both in education, creativity and art; (3) constraints in the application of the learning model: lack of teacher understanding of the learning model, lack of learning media, school differences, facilities and financial constraints, and lack of students. Abstrak Peneliti mengkaji lebih dalam tentang model pembelajaran bimbingan belajar untuk mengetahui model pembelajaran yang digunakan guru dalam proses pembelajaran di Saddhāphala Jaya Krecek. Penelitian ini menggunakan metode kualitatif deskriptif. Teknik dan instrumen pengumpulan data yang digunakan yaitu menggunakan teknik wawancara, observasi, dan dokumentasi. Teknik keabsahan data melalui pengamatan terus-menerus, tiangulasi, dan member check. Data dianalisis dengan menggunakan metode Miles and Huberman yaitu pengumpulan, reduksi data , penyajian data, dan penarikan kesimpulan atau verifikasi data. Hasil dari penelitian ini bahwa pembelajaran yang dilakukan di Saddhāphala Jaya Krecek meliputi tahap pembukaan (Namakārapāṭha), pemaparan materi, dan penutup atau evaluasi; (2) model yang digunakan oleh guru tergantung pada kegiatan yang dilakukan baik dalam pendidikan, kreativitas, dan kesenian; (3) kendala dalam penerapan model pembelajaran: kurangnya pemahaman guru pada model pembelajaran, media pembelajran masih kurang, perbedaan sekolah, keterbatasan fasilitas dan keuangan, dan kurangnya semagat dari siswa.